Advancement of emerging technologies for non-destructive measurement of water and non-aqueous phase liquid saturation in porous media: A review - Kapil Kumar; Harris Ramli (Desalination and Water Treatment)
Groundwater is essential for freshwater supply, but purifying it from pollution caused by human and natural activities is complex. Accurate determination of contamination extent and pollutant levels, such as wastewater and Non-Aqueous Phase Liquids (NAPLs), is vital due to their detrimental effects on porous media. The presence of NAPLs, exacerbated by industrial activities, leaks, and spills, demands effective detection and measurement for environmental safety. Traditional methods like drilling are invasive, slow, and costly. In contrast, Non-Destructive Methods (NDMs) such as X-rays, Electrical Resistivity Imaging, Ground-Penetrating Radar, and various imaging techniques provide faster, more cost-effective, and precise detection of NAPLs in soil. This paper explores the advantages of both in-lab and field NDMs, advocating for their use over traditional techniques due to their efficiency and lower long-term costs. It highlights the Simplified Image Analysis Method (SIAM) for its accuracy and user-friendliness. The paper also recommends further research into different soil conditions and weather patterns to enhance these methods. A review of over 250 publications underscores the growing preference for image analysis methods, particularly SIAM, for effectively measuring NAPL and water levels across various conditions. This research aims to guide the selection of optimal techniques for environmental studies and advance geotechnical knowledge.